(untitled) (Law and world, 2023)
After the Civil Code of Georgia entered into force in 1997, more than 25 years, the analog of the German family law at that time – Georgian family law – has not become the object of legislative changes. While all over Europe, around the fundamental core of so- ciety called the family, the states establish new regulations, create institutions, expand the concepts and support all this to the free de- velopment and choice of the individual, our family law is more and more distant from reality. In this article, the types of relationships between couples provided by the French Civil Code, different from marriage, are reviewed, which, according to the French national statistics, are much more in demand among young couples than marriage. These types allow individuals to decide of their own free will which legal institution is the most favorable for their relationship and goals. Georgian society belongs to the big family of Europe, that is why it is necessary for the legislation of Georgia to follow the dynamics of European development and take into account the changes made by the neighboring states, of course, adjusting it to its reality. Keywords: family law, marriage, cohabitation, act of solidarity, couple Introduction The family is the nucleus of Georgian and French society, which is organized and protected by law due to its high importance. The family is a large or small group of natural persons who have some kind of kinship or family-legal relationship with each other. The French Civil code, in contrast to the Georgian law, which only recognizes the existence of the institution of marriage between a couple, recongnizes two legal forms of a couple’s relationship: cohabitation (concoubinage) and act of solidarity (Pacte civil de solidarité*). As a result of many parliamentary debates, the Chapter on cohabitation and the act of solidarity was added to the French Civil Code on November 15, 1999, based on Law No. 99-944. The development of society caused the aforementioned legislative change, women’s movements, and the establishment of women’s rights, the desire for an independent life, and personal freedom. According to French National Institute of Statistics research, cohabitation and act of solidarity are significantly more common among young couples than marriage.[1] Cohabitation Unlike the act of solidarity, cohabitation in the French civil code is devoted to only one article (Article 515-8), according to which cohabitation is the fact of living together between two persons of different sexes or of the same sex, which is characterized by stability and continuity.[2] For a couple’s life together to be considered cohabitation, it is necessary that their stay together be characterized by the following conditions: Two authorized persons must represent the couple; Not married; Lived together with minimal stability; Their relationship should be characterized by continuity. The French Civil Code recognizes cohabitation only as a fact and does not give it legal force; cohabiting persons are not even considered members of the same family, and their relationship status is single.* Despite this, a person can live in only one cohabitation (concoubinage). The French Civil Code does not set an age limit for cohabitation therefore, even minors can live together as a couple under cohabitation. By integrating cohabitation into the French Civil Code, the legislator did not create a new institution; it simply recognized the right of the couple to have a free union (union libre), but outside of the relationships regulated in detail by the Civil Code. Nevertheless, Article 515-8 of the French Civil Code has often become the basis for decision-making by the French Supreme Court. Despite the law limiting cohabitation to only one article, jurisprudence has established various principles. Since, according to French legislation, cohabitation is a legal fact, its registration, unlike marriage, is impossible, but it is possible for the state body to recognize the fact. The City Hall[3] will issue the notification about cohabitation, although it is not obliged to issue such a document by law. According to the official website[4] of the state services, based on the couple’s request for a certificate of cohabitation, some City Halls issue a document and determine the existence of the fact of cohabitation. This document does not have legal force; it is more like a certificate and can be used in some cases defined by law, for example, when a couple requests social assistance. Obtaining a certificate is free of charge, and to receive it, the couple must submit identity cards and residence documents (utility payment receipt, rental agreement, etc., which is, in a way, an alibi of the couple’s cohabitation). It may also be necessary to present witnesses who will confirm that the couple is living together. Although cohabitation does not create a legal relationship between the couple, it does not entirely exclude them either. For example, a partner can demand from the other partner the return of the property obtained due to unjust enrichment,[5] since they do not have mutual maintenance obligations. According to the decision[6] of the French Supreme Court, a cohabiting couple does not have an obligation of fidelity. Since cohabitation is a free relationship, separation can occur at the initiative of one party without the other party's consent, without his knowledge, and without any legal measures or appeal to the state authorities. The pregnancy of the partner is also not an obstacle to separation, as it is considered, for example, in marriage, however, in the presence of certain circumstances, based on Article 1240 (formerly Article 1382) of the French Civil Code, which deals with the question of compensation for damages caused by tortious obligations, after infidelity and separation, it is possible to claim compensation for moral damages against the spouse who initiated the breakup or was the author of the betrayal.[7] During cohabitation, if one of the partners dies, the other party has no right to legal inheritance. However, it is possible to be a testamentary heir, and the partner does not have the right to reversion* of the deceased partner's pension. Act of solidarity The act of solidarity is a contract between two adults. In its essence, the act of solidarity, which the french refer to as PAX (P.a.c.s), lies between cohabitation and marriage and concerns the property and money matters of the couple; it does not affect the family and filiation. According to the Franch public services website, Pax affects a couple’s social, income, tax, housing, and property rights and does not affect filiation or name. Under the act of solidarity, partners are not considered to be spouses of each other, and whether they are members of the same family or not, neither the law nor the doctrine nor the jurisprudence has an unequivocal answer. The articles on the act of solidarity of the French Civil Code have undergone several changes since 1999, namely in 2005 and 2006. According to the first sentence of Article 515-4 of the French Civil Code, a couple bound together by an act of solidarity undertakes to live together and support each other materially and mutually. According to data published by the French institute of Statistics and National Studies on January 16 in 2018, 181,900 different-sex couples and 7,000 same-sex couples signed the act of solidarity in 2015, and 184,400 different-sex couples and 7,100 same-sex couples in 2016. This data shows the fact that the act of solidarity is a sought-after institution in French society. The act of solidarity is not only characteristic of French law; a similar type of institution is also found in Belgian law under the name of legal cohabitation (cohabitation légale), which differs in its content from the institution of the French act of solidarity. According to Belgian law, legal cohabitation can even be enjoyed by members of the same family; the couple doesn't need to be in a sexual relationship, and the partners in legal cohabitation undertake to manage the residence together, take care of living expenses together and share certain debts. In German law, the institution of the French solidarity act can be found under the name of cohabitation (Lebenspartnerschaft). However, the content is different in particular, a couple is only homosexual, they undertake to take care of each other and live together they have the right to take each other’s surname. Unlike French civil law, the German Civil Code gives cohabiting partners more rights and obligations, almost similar to that of a married couple. German law gives the cohabiting partner the right to adopt the biological child of the other partner, which is impossible under the French Civil Code. Canadian civil law recognizes cohabitation under the name of living common law, while some American states recognize - common-law marriage. However, the content of each institution and regulation by law is not similar. Common-law marriage in the United States was based on the New York Supreme Court’s decision in 1809 (Frenton v. Reed), in which the court notes that a couple who have lived together for several years and are perceived as husband and wife in the eyes of the public, are considered married even without a formal marriage, and they are spouses for each other. According to Article 515-1 of the French Civil code, the act of solidarity is a contract between two adults, of the same or different sex, for the organization of their common life. Signing a so-called Pax contract is prohibited if one (or both) partners are already married or are “Paxed“. Incest is strictly prohibited by French law. According to Article 515-2 of the French Civil Code, the act of solidarity is void if it is concluded between relatives in direct ascending and descending lines and between relatives in lateral lines (cousins) and their children and grandchildren. Since the act of solidarity is a contract signed between the partners, it becomes effective for the parties upon its signature, and the right of dispute for the third parties arises upon its publication by the notary. The contract is filed before a civil officer, who first verifies the admissibility of the couple’s applications and then registers it and delivers the documents to a notary for registration and subsequent publication. If the parties, after the publication of the contract, want to make changes to the act of solidarity, they are obliged to register them through the procedure of entry into force of the contract. Two types of the contract act of solidarity exist: 1. Prepared in advance by the City Hall[8] and 2. Drawn up by the free will of the parties, and the principle of freedom of contract applies to it. According to the first sentence of Article 515-5 of the French Civil Code, if the contract does not provide otherwise, the parties dispose of personal belongings according to their interests and wishes. Also, the payment of the loan taken by one partner for personal interests is only his obligation. If one of the partners took the loan for common interests, the other partner is also responsible for paying. If one of the partners dies, another party has no right to inherit without a will. According to the French Civil Code, if the heir bequeaths part of his property to his partner, he is obliged to bequeath the other party of the property to the legal heirs.[9] Partners have the right to end the act of solidarity independently, and the relationship will be considered completed for the couple from the moment of registration of the contract's termination statement by one of the partners. According to the French law of May 12, 2009, the Family Court is authorized to hear the claim if a dispute arises between a couple. Conclusion Marriage is a significant fact in the life of any person and gives rise to important legal, moral responsibilities and obligations. According to Article 30 of the Constitution of Georgia, marriage, as a union between a man and a woman to create a family, is based on the legal quality and free will of the spouses. For a long time, the fact of a couple living together without marriage is no stranger to Georgian society; however, since Georgian law does not consider any other fact or institution of a couple being together besides marriage, the relationship of the parties remains without legal regulation or recognition of this relationship by the law, which unfortunately causes many problems, especially in case of separation of the couple. Since a couple's relationship in an unregistered marriage is not legally recognized, the parties cannot enjoy a number of rights, which threatens their personal and property rights. The Georgian Civil Code must consider the example of the French Civil Code and integrate institutions other than marriage, such as the act of solidarity, into the Civil Code. By integrating this institution into the law, the couple will have the opportunity to decide how to legally regulate the relationship between them. Also, recognizing cohabitation as a fact by the law and bringing it into a particular legal framework will be an important innovation since the couple will have the opportunity to recognize the fact of their cohabitation before the law, which will to some extent, bring legal recognition of their relationship. Since the supreme law of the country strictly defines marriage as a union between a man and a woman, it is possible to regulate the institution of the act of solidarity or the fact of cohabitation, allowing a same-sex couple to regulate their monetary and property relations. In addition, if the law allows a same-sex couple to enjoy the act of solidarity or the fact of cohabitation, in this way, their relationship will be recognized and brought into the legal framework, and the institution of the family will not be violated. Since the law is a living organism and constantly undergoes changes due to the development and needs of the society, the Georgian Civil Code must follow the rhythm of developed countries, integrate such legal issues, and adapt to the society's demands already been introduced and tested. Bibliography Constitution of Georgia of August 24, 1995; Civil Code of Georgia of June 26, 1997; Law of Georgia on Civil Acts of December 20, 2011; The Civil Code of France of March 21, 1804; Aline Cheynet de Beaupré Family Law; Paris, Ellipses, 2019; J. Carbonnier Civil law – the family; Puf; 21st ed. 2003; P. Coubre, A. Gouttenoire and M. Farge – Family Law; Sirey, 8th ed. 2021; Decision of the French Supreme Court of May 18, 2022 N 18-12.808; Decision of the French Supreme Court of February 3, 1999 N 96-11946;10.www.service-public.fr. Footnotes *Civil Pact of Solidarity. [1] https://www.insee.fr/fr/statistiques/3306175#tableau-figure1. [2] Article 515-8 du Code civil - Le concubinage est une union de fait, caractérisée par une vie commune présentant un caractère de stabilité́ et de continuité́, entre deux personnes, de sexe diffèrent ou de même sexe, qui vivent en couple. *In French Doctrine, only the persons who have sexual relations with each other are referred to as a couple. [3] In France, City Hall is a body where any information about a person is registered. [4] https://www.service-public.fr/particuliers/vosdroits/F1433. [5] Decision of the French Supreme Court of May 18, 2022 N 18-12.808. [6] Decision of the French Supreme Court of February 3, 1999 N 96-11946. * Le droit à la pension de réversion. [7] Tout fait quelconque de l’homme, qui cause à autrui un dommage, oblige celui par la faute duquel il est arrivé à le réparer - Any action that causes harm to another obligates the author of that action to correct it. [8] https://www.formulaires.service-public.fr/gf/cerfa_15725.do. [9] https://www.service-public.fr/particuliers/vosdroits/F2529.